Association of the Polymorphism rs13259960 in SLEAR With Predisposition to Systemic Lupus Erythematosus. Issue 6 (26th April 2020) - Fan, Zhen; Chen, Xiaowei; Liu, Lu; Zhu, Caihong; Xu, Jinhua; Yin, Xianyong; Sheng, Yujun; Zhu, Zhengwei; Wen, Leilei; Zuo, Xianbo; Zheng, Xiaodong; Zhang, Yaohua; et al.
Abstract : Objective: Genome‐wide association studies have identified many susceptibility loci for systemic lupus erythematosus (SLE). However, most of these loci are located in noncoding regions of the genome. Long noncoding RNAs (lncRNAs) are pervasively expressed and have been reported to be involved in various diseases. This study aimed to explore the genetic significance of lncRNAs in SLE. Methods: A genome‐wide survey of SLE risk variants in lncRNA gene loci was performed in Han Chinese subjects (4, 556 with SLE and 9, 451 healthy controls). The functional relevance of an SLE risk variant in one of the lncRNA genes was explored using biochemical and molecular cell biology analyses. In vitro loss‐of‐function and gain‐of‐function strategies were used to clarify the functional and phenotypic relevance of this SLE susceptibility lncRNA. Moreover, correlation of this lncRNA with the degree of apoptosis in the peripheral blood of SLE patients was evaluated. Results: A novel SLE susceptibility locus in a lncRNA gene, designated SLEAR (for SLE‐associated RNA), was identified at the single‐nucleotide polymorphism rs13259960 (odds ratio 1.35, P combined = 1.03 × 10 −11 ). The A>G variation at rs13259960, located in an intronic enhancer, was found to impair STAT1 recruitment to the enhancer that loops to the SLEAR promoter, resulting in decreased SLEAR production in peripheral blood mononuclear cells from patients with SLE (3 with the G/G genotype, 22 with A/G, and 103 with A/A at rs13259960; P = 0.0241). Moreover, SLEAR interacted with the RNA binding proteins interleukin enhancer binding factor 2, heterogeneous nuclear RNP F, and TATA‐binding protein–associated factor 15, to form a complex for transcriptional activation of the downstream antiapoptotic genes. In addition, SLEAR regulated apoptosis of Jurkat cells in vitro, and its expression level was correlated with the degree of cell death in the peripheral blood of patients with SLE (r = 0.824, P = 2.15 × 10 −8 ; n = 30). Conclusion: These findings suggest a mechanism by which the risk variant at rs13259960 modulates SLEAR expression and confers a predisposition to SLE. Taken together, these results may give insights into the etiology of SLE.